Introduction English for Mathematics Course: What are the Student Difficulties and Causing Factors? - Cesaria, Anna; Kemal, Edwar; Adnan, Mazlini (VELES Voices of English Language Education Society, 2024)
English for Mathematics is a required university course designed to bridge the gap between general English proficiency and the specific linguistic demands of mathematics. This study aims to explore the challenges students face in adapting to this specialized curriculum, aiming to deepen our understanding of the educational hurdles posed by evolving academic requirements for graduates. Employing a descriptive qualitative research design, the research examines the experiences of 35 students enrolled in the English for Mathematics course at the Mathematics Study Program of Universitas PGRI Sumatera Barat. Data were collected through semi-structured questionnaires, revealing five principal areas of difficulty: listening, reading, writing, and speaking skills, along with comprehension of mathematical content. The study identifies several factors contributing to these challenges, including limited vocabulary, inadequate prior knowledge, misinterpretations of course material, a lack of effective learning aids, and frequent writing errors. The findings suggest that these obstacles hinder student performance and impact their engagement and satisfaction with the course. The study calls for targeted interventions by educators and curriculum designers to enhance instructional methods and learning materials, thereby improving student outcomes and making learning more engaging and effective. These insights have broader implications for curriculum development and instructional strategies in specialized English education settings.